The Effects of The Cash Transfer Programme for Poor Students on Childs Work Participation: Evidence from Java (Indonesia) - Achsanah Hidayatina (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2018)
Cash transfer is considered as a relatively safe policy instrument to improve child welfare. Over the past ten years, Indonesia has made major progress in reducing the number of children involved in child work. It has done so primarily by expanding education provision to increase the time children spend in school and reduce the time children allocate to work. This progress has been supported by the implementation of poverty alleviation programmes that provided income assistance to vulnerable families. This paper aims to analyse whether cash transfer subsidies provided by the Government of Indonesia were sufficient for children to decrease the probability of working and reduce the hours of working activities of children within households. This paper includes a detailed exploration of differences in impacts by childrens gender and areas of residence. This paper uses cross sectional data to analyse the effects of the programme on childs work. The data covers children aged from six to 14 from the Indonesian Family Life Survey (IFLS) in 2014. The data is non-experimental and programme participation is not randomly assigned. The bivariate Probit with endogenous dummy models are also estimated for the probability that a child is working, controlling for additional characteristics of the child, head of household, household and community-level characteristics. The results of this paper are particularly relevant for understanding the role of cash transfer programmes in developing countries. The findings of this paper suggest that the Government of Indonesia needs to reach the poorest children who are out of school.